2013
DOI: 10.1038/jp.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

A standardized nutrition approach for very low birth weight neonates improves outcomes, reduces cost and is not associated with increased rates of necrotizing enterocolitis, sepsis or mortality

Abstract: Implementation of a standardized approach to nutrition in VLBW infants reduces the use of PN thereby reducing cost, causes a more rapid regain of birth weight, decreases the number of babies that are small for gestational age and microcephalic at discharge, and decreases the time to full enteral feeds. No adverse increases in mortality, sepsis, NEC, coagulase-negative Staphlococcal infections or line infections occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
1
37
0
5
Order By: Relevance
“…Basing feeding decisions on gastric residuals in the neonate is challenging, as there is considerable overlap in residual characteristics among those with and without pathology 12 . ‐ 14 Regardless, feeding protocols that detail both evaluation of and suggested clinical response to gastric residuals can still allow for improved feeding outcomes in neonatal populations 15 …”
Section: Question 3: What Clinical Factors Should Be Assessed To Detementioning
confidence: 99%
See 1 more Smart Citation
“…Basing feeding decisions on gastric residuals in the neonate is challenging, as there is considerable overlap in residual characteristics among those with and without pathology 12 . ‐ 14 Regardless, feeding protocols that detail both evaluation of and suggested clinical response to gastric residuals can still allow for improved feeding outcomes in neonatal populations 15 …”
Section: Question 3: What Clinical Factors Should Be Assessed To Detementioning
confidence: 99%
“…Nutrition protocols have been effective quality improvement interventions, reducing the time to achieve nutrition goals, including transitioning off PN to full EN, while also lowering costs 24 , 25 . In a large tertiary pediatric institution, the development and implementation of PN guidelines resulted in a marked reduction in PN courses that lasted less than 5 days, a cutoff that the authors used as an indicator of inappropriate PN use 21 .…”
Section: Question 14: How Should Healthcare Organizations Track/monitmentioning
confidence: 99%
“…Studies have shown that the use of preterm feeding protocols in the NICU can improve feeding tolerance and decrease the risk for NEC . They have also shown reduced PN use and days to full feeds, reduced late‐onset sepsis, fewer line days, and improved growth . The focus of our study was to measure the neonatal outcomes from use of a nutrition protocol during the NICU stay.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] They have also shown reduced PN use and days to full feeds, reduced late-onset sepsis, fewer line days, and improved growth. [18][19][20][21] The focus of our study was to measure the neonatal outcomes from use of a nutrition protocol during the NICU stay. Our primary outcome measures were to see if a nutrition protocol made a difference in growth outcomes (weight, length, and head circumference), the number of days made nil per os (NPO) after feeding initiation, PN days, and NEC.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, a NICU feeding protocol decreased PN duration by approximately 5 days, in turn leading to a significant reduction in cost: approximately $385,000 in hospital savings in 1 year. 75 …”
Section: Cost Of Pn Complicationsmentioning
confidence: 99%